2017
DOI: 10.3390/catal7040107
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Polymer-Supported Terpyridine–Palladium Complex for the Tandem Aminocarbonylation of Aryl Iodides to Primary Amides in Water Using NaN3 as Ammonia Equivalent

Abstract: Primary aromatic amides are valuable compounds, which are generally prepared via Beckmann rearrangement of oximes and the hydration of nitriles in organic solvents. We investigated the environmentally friendly catalytic aminocarbonylation in water. Thus, a novel heterogeneous transition-metal catalyst, a polymer-supported terpyridine-palladium(II) complex, was prepared and found to promote azidocarbonylation of aryl iodides with NaN 3 and to reduce the generated benzoyl azides in water under CO gas to yield pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the absence of any further additive, yields of up to 90 % were observed. Mechanistic studies suggested a dual role of the catalyst – participation in the azidocarbonylation and the subsequent Staudinger‐type reaction …”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“…In the absence of any further additive, yields of up to 90 % were observed. Mechanistic studies suggested a dual role of the catalyst – participation in the azidocarbonylation and the subsequent Staudinger‐type reaction …”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“…However, an efficient homogeneous CC coupling, as well as an aminocarbonylation reaction, are often restricted, due to the limited solubility of reagents (substrates, amine nucleophiles) and amide products or the decomposition of the catalyst. Consequently, many more heterogeneous [ 16 , 17 , 18 , 19 , 20 , 21 ] or biphasic [ 22 ] aminocarbonylation processes have been described than homogeneous processes [ 23 , 24 , 25 ]. Additionally, it has been described by our research group that water can act as an O -nucleophile during aminocarbonylative conditions, resulting in the formation of carboxylic acid when low-reactive nucleophile reaction partners are used [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, we have developed amphiphilic polystyrene-poly(ethylene glycol) (PS-PEG) resin-supported terpyridine-palladium complexes that promote varied catalytic transformations [18][19][20][21][22][23][24][25][26][27][28] smoothly in water [29][30][31][32] under heterogeneous conditions [33][34][35][36]. Herein, we aimed for the Friedel-Crafts reaction of π-allylic palladium intermediates with indoles in water under aerobic conditions in the presence of amphiphilic PS-PEG resin-bound pyridine skeleton ligand-palladium complexes 1a-c (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%